Efforts to Create Transformative Diakonia Through Entrepreneurs Influenced by Servant of God Leadership and The Role of Congregational Members - Johnson P. Robinsar Siregar; Teddi Paul Sihombing; Humala Lumbantobing; Heryanto Heryanto (Green Publisher Indonesia, 2022)
The research objective was to prove the influence of God's Servant Leadership and the Role of the Congregation on Diakonia Transformation through Entrepreneurship. The research was conducted on 80 samples of the Servant of God and members of the congregation around the City of Pematangsiantar, Province North Sumatra using simple random sampling. Data collection using google form with a questionnaire. The study used SEM-PLS to process data for testing validity, reliability and hypothesis testing. Research proves that the influence of God's Servant Leadership and the Role of the Congregation has a very big influence on entrepreneurship in realizing the Transformative Diakonia. Thus, the influence of God's Servant Leadership and the Role of the Congregation is very large and has a direct impact through entrepreneurship to create a Transformative Diakonia. The research recommends three things; first, as a solution to the development of church services in dealing with problems that occur both in the church and in the community. Second, it is important to develop effective and significant leadership of the Servant of God in realizing the ministry of the Transformative Diakonia. Third, the results and research outputs explain that the Transformative Diakonia ministry is very important for church ministry.